Unfulfilled expectations and labor market interactions: A statistical equilibrium theory of unemployment - Ellis Scharfenaker; Duncan K. Foley (The University of Utah, Department of Economics, 2021)
We examine the equilibrium wage and employment outcomes in a labor market model comprised of informationally constrained workers and employers whose labor market interactions have a non-zero impact on wages. The model endogenizes employment interactions between workers and employers in terms of a quantal response equilibrium and produces an equilibrium level of frictional unemployment as a statistical feature of a decentralized labor market. Shocks to the economy can produce short-run equilibrium involuntary unemployment arising from unfulfilled expectations. Even after agents align their expectations with market outcomes, unless they also adjust their expectations of the scale of statistical fluctuations in wages, a negative shock to demand can result in higher levels of equilibrium unemployment. In this way the model exhibits a particular type of non-neutrality of money in the short-run and long-run.
Keywords: C18; D80; E10; E24; E70; 330; Unemployment; Unfulfilled expectations; Wage distribution; Labor market; Statistical equilibrium